2017
DOI: 10.3390/ijms18020246
|View full text |Cite
|
Sign up to set email alerts
|

Mblk-1 Transcription Factor Family: Its Roles in Various Animals and Regulation by NOL4 Splice Variants in Mammals

Abstract: Transcription factors play critical roles in regulation of neural development and functions. A transcription factor Mblk-1 was previously reported from a screen for factors possibly important for the higher brain functions of the honeybee. This review first summarizes how Mblk-1 was identified, and then provides an overview of the studies of Mblk-1 and their homologs. Mblk-1 family proteins are found broadly in animals and are shown to affect transcription activities. Studies have revealed that the mammalian h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…MBR-1, another homologue of Mblk-1 in the nematode Caenorhabditis elegans, was also reported to have neuronal functions, in which it is required for the pruning of specific neurites that occur during larval development (Kage et al, 2005). Moreover, it was also shown that MBR-1 is required for olfactory plasticity in adult animals (Hayashi et al, 2009;Takayanagi-Kiya et al, 2017). Taken together, we deduce that Mblk-1 may be involved in the regulation of behavioral plasticity of honey bee through its target gene ame-miR-279a in the MBs.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
“…MBR-1, another homologue of Mblk-1 in the nematode Caenorhabditis elegans, was also reported to have neuronal functions, in which it is required for the pruning of specific neurites that occur during larval development (Kage et al, 2005). Moreover, it was also shown that MBR-1 is required for olfactory plasticity in adult animals (Hayashi et al, 2009;Takayanagi-Kiya et al, 2017). Taken together, we deduce that Mblk-1 may be involved in the regulation of behavioral plasticity of honey bee through its target gene ame-miR-279a in the MBs.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
“…2A,B ). Through these motifs LCoR interacts with different hormone-bound nuclear receptors attenuating their transcriptional activity 49 , 50 . Likewise, B .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the ecdysone ‐regulated gene Mblk‐1 (Figure ) as the best‐segregating gene at the significant locus suggests a potential pathway for resistance in the Toulouse population of Varroa ‐resistant Apis mellifera . The regulation of metamorphosis by ecdysone and Mblk‐1 is conserved across both holo‐ and hemi‐metabolous insects (Takayanagi‐Kiya, Kiya, Kunieda, & Kubo, ; Ureña, Manjón, Franch‐Marro, & Martín, ). As Varroa incorporates honey bee pupal proteins into its developing oocytes (Tewarson, ) and has been experimentally shown to suspend reproduction when pupal cues, related to the initiation of morphogenesis, are not optimal (Frey et al, ), a small change in the structure or expression of Mblk‐1 could induce Varroa to suspend reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Varroa feeds on the pupa's fat bodies (Ramsey et al, ) where expression of the Drosophila homolog of the Mblk‐1 gene increases during the pre‐pupal phase (Baehrecke & Thummel, ). With the role of Mblk‐1 in metamorphosis being higly conserved in insects (Takayanagi‐Kiya et al, ; Ureña et al, ), this raises the possibility that Mblk‐1 and the pulse of pre‐pupal ecdysteroids are not a cue but a necessary physiological component for the successful initiation and timing of reproduction in Varroa . Our findings support this as the expression of Mblk‐1 , Phantom (Figure a,c) and, by proxy, ecdysone titres in the drone pupae peaks around the same time as the Varroa mother's early meals and the initiation of vitellogenesis.…”
Section: Discussionmentioning
confidence: 99%